2017
DOI: 10.1371/journal.pone.0175925
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of tuberculosis and diabetes mellitus comorbidity: A systematic review

Abstract: IntroductionThe dual burden of tuberculosis (TB) and diabetes mellitus (DM) has become a major global public health concern. There is mounting evidence from different countries on the burden of TB and DM comorbidity. The objective of this systematic review was to summarize the existing evidence on prevalence and associated/risk factors of TBDM comorbidity at global and regional levels.MethodsOvid Medline, Embase, Global health, Cochrane library, Web of science and Scopus Elsevier databases were searched to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
133
7
26

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(192 citation statements)
references
References 76 publications
26
133
7
26
Order By: Relevance
“…Although the focus of our review was different from that of Workneh et al, and despite a significant variation in the included studies, our report produced strikingly similar regional coprevalences, each lending credence to the other . Due to differences in search strategy and inclusion criteria, this article includes 38 studies that are not included in Workneh et al's review.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Although the focus of our review was different from that of Workneh et al, and despite a significant variation in the included studies, our report produced strikingly similar regional coprevalences, each lending credence to the other . Due to differences in search strategy and inclusion criteria, this article includes 38 studies that are not included in Workneh et al's review.…”
Section: Discussionmentioning
confidence: 67%
“…Although the focus of our review was different from that of Workneh et al, and despite a significant variation in the included studies, our report produced strikingly similar regional coprevalences, each lending credence to the other. 20 This review also demonstrated that many TB-DM studies in LMICs take place in urban, tertiary care centres. As such, many low-income populations in these countries, such as rural dwellers and those who do not receive care in large referral settings, were largely absent from this analysis, which reflects the fact that most global DM research includes only higher-income urban populations.…”
Section: Middle Eastmentioning
confidence: 75%
See 1 more Smart Citation
“…[8,9] Workneh MH et al systemic review shows an overall global median DM prevalence of 16% (IQR 9.0 -25.3%). [10] Proportion of DM among Patients with different Bacillary Load This study shows proportion of DM was higher among patients with high bacillary load. Matthew J Magee et al shows that patients with TB and DM were more likely to have a higher AFB smear grade (aOR 2.37, 95% CI 1.14 -4.94).…”
Section: Proportion Of Dm Among Pulmonary Tuberculosis Patientsmentioning
confidence: 73%
“…The risk factors for DM-TB comorbidity are represented by male gender, old age, marital status, smoker status, alcohol consumption, physical inactivity, urban environment, crowded areas, insanitary conditions, low educational level and reduced economic status [6][7][8][9][10][11]. Patients with DM and TB have a family history of TB, family history of DM, higher body mass index and decreased glycemic control [6,7]. Also, they are predisposed to pulmonary cavities, hemoptysis and sputum positive at diagnosis, which persist positive after one or two months of treatment [5].…”
mentioning
confidence: 99%